Effect of long-term application of sewage sludge and farmyard manure on soil properties under mustard-based cropping system - Mahesh C Meena; KP Patel (Journal of Oilseed Brassica, 2026)
The use of sewage sludge in agriculture is being considered as one of the method for recycling of waste in an environmentalbeneficial manner. Sewage sludge, due to its acidic nature, high organic matter and heavy metals content, had moreimpact on soil properties. To study the changes in the selected physical and biological properties and accumulation andmobility of heavy metals due to continuous use of sewage sludge, a field experiment was started in year 2000 to evaluatethe long-term effect of sewage sludge with or without farmyard manure under pearlmillet (Pennisetum glaucum L.) (cv.GHB-526) and Indian mustard (Brassica juncea L. Czernj and Cosson) (cv. GM-2) crops sequence. The sewage sludge@10 and 20 tonnes/ha, farmyard manure @ 10 tonnes/ha and farmyard manure + sewage sludge @ 10+2.5, 10+5 and10+10 tonnes/ha were applied to pearlmillet in kharif for direct effect and their residual effect was studied on Indianmustard during rabi in randomized block design keeping three replications. Use of sewage sludge increased the heavymetal contents in surface soil as well as plant. The DTPA-extractable heavy metals were higher in sewage sludge thanfarmyard manure + sewage sludge or farmyard manure treated soil. The farmyard manure + sewage sludge applicationreduced bulk density and increased saturated hydraulic conductivity, microbial biomass carbon (MBC), microbial biomassnitrogen (MBN) and dehydrogenase activity (DHA) significantly. The microbial activity was decreased by sewagesludge alone compared to farmyard manure + sewage sludge or farmyard manure. The farmyard manure and sewagesludge applications were also found beneficial in increasing yield and quality of grain as direct effect on pearlmillet andas residual effect on succeeding Indian mustard. Application of farmyard manure together with sewage sludge exhibitedmitigating effect by lowering the contents of trace and heavy metals in both the crops.